Editorial Policy and the Dissemination of Scientific Knowledge on Open Access—Case Study: Science Communication Journals in Latin America - Sánchez-Pita, Fernando; Benito-Cabello, Mario; Puebla-Martínez, Belén (Publications, 2025)
The editorial policies of science journals have an impact on access to scientific knowledge. One of the most effective ways to share knowledge with the entire society is to offer it free of charge. Considering the international recognition of Scopus and Web of Science, this study analyses 28 scientific journals in the field of communication that are indexed under the “Communication” category in both databases in order to review their editorial decisions regarding the dissemination of articles they publish. By taking a descriptive approach, the authors have examined the inner workings and design, as well as aspects related to ethics and transparency, as key components of this policy. The findings indicate that most journals are influenced by digital publishing platforms and that various features examined in this study are offered by these platforms by default. This is especially true in terms of design, which simultaneously enables yet influences each journal’s editorial policy. Together with the need for financial support and adequate human resources, this situation makes it difficult to implement an editorial policy free of external encroachment. This article concludes by emphasising the importance of establishing editorial policies that promote open access as a standard practice, thereby reinforcing the democratisation of access to scientific knowledge. It is recommended to strengthen institutional support for journals operating under the diamond model, promote their visibility and thematic specialisation, enhance technical and visual aspects, and clearly articulate ethical commitments within their editorial policies. In short, this analysis provides a comprehensive overview of both strengths and areas of improvement, offering recommendations to help these journals optimise their contribution to the global academic ecosystem.
Keywords: open access; scientific journals; ethics; Scopus; Web of Science